Shaping individual paths for decision-making: a fuzzy set approach of religious and humanistic beliefs leading to the (non)acceptance of euthanasia - Soares, Maria Eduarda; Teixeira, Alfredo; Tavares, Patrícia (International journal of organizational analysis (2005), 2023)
Purpose While the influence of individual beliefs on decision-making has been widely acknowledged, the interaction of different types of beliefs remains an under-researched topic. This study analyses how the simultaneous influence of religious beliefs and nonreligious beliefs shapes individual decision-making. This study aims to contribute to inform organizational decisions on topics potentially associated with these two types of beliefs, including corporate social responsibility matters. This study also aims to provide insights to ethical decision-making in situations of absence of social consensus, a subject that is relevant for individuals, organizations and policymakers. Design/methodology/approach This study uses fuzzy set qualitative comparative analysis to identify how different configurational groupings of Christian beliefs and humanistic beliefs lead to the acceptance or nonacceptance of euthanasia in a sample of individuals who identify as Catholic. Findings Among individuals sharing a Catholic religious affiliation, the authors identify three different configurations of beliefs – Cultural Catholics (religious beliefs are absent and humanistic beliefs are present), Observant Catholics (religious beliefs are present and humanistic beliefs are irrelevant) and Secular Catholics (both religious beliefs and humanistic beliefs are present). Originality/value Previous research has put forward the role of religion-related variables, such as religious affiliation and level of religiosity, for views on euthanasia. This study provides a more detailed analysis of the role of belief systems, identifying how different configurational groupings of beliefs lead to a decision grounded in moral and ethical considerations but for which there is an absence of social consensus.